Human Proteome Project and Current Bioinformatics Status in Disease Diagnosis and Treatment - Anwar, Pervez; Javed, Ayesha; Amjad, Izba; arif, Iqra; sadiqa, Attiqa; akram, Huria; azhar, Laraib (Journal of Proteomics and Genomics Research, 2018)
Human proteome project was revolutionized about 40 years ago with purpose of summarizing whole proteomic data at one place. It was launched after human genome project to map and observe all proteins. The goal related proteomic study is to draft the entire human proteome in disease diagnosis by using bioinformatics tools. Pillars of human proteome project provide different databases related to proteins at transcriptional and translational level. Human proteome organization(HUPO) published biology disease HUPO whose aim is to measure protein and proteome by life and processes related to human diseases. Different human organ like plasma, liver, brain and diabetic base project are used to characterize human disease and health. Major data resources accumulated in databases like peptides Atlas, GPMDB and neXtProt for proteins. Matrices of human proteome project identify and characterize the protein products as Post translational modification (PTM), splice various isoforms from 20,300 proteins. Matrices related to different years make proteomes counterpart by magnify the research biomedical community with high output of instruments and specimen pre-analytical protocols. CALIPHO multidisciplinary group provides information about protein complexities, interactions, function and structure complexities after Uniport and Swissprot. Different bioinformatics tools are used for structural and functional annotations of protein, disease diagnosis and mutations due to protein. Extensive study of human proteome project has been proved helpful in disease treatment at translational and post- translational levels. In future, human proteome project along with bioinformatics will include protein profiling, biomarkers, Mass spectrophotometer technique and cross analysis of different proteome projects.
Keywords: Current bioinformatics status; Disease diagnosis; In-silico approaches; Human Proteome Project; CALIPHO